A Random Trial Comparing Mitomycin C and Autograft of Conjunctiva After Excision of Primary Pterygium (Medical Forum Monthly, 2021)
Objective: To study a random trial comparing mitomycin C and autograft of conjunctiva after excision of primary pterygiumStudy Design: Prospective studyPlace and Duration of Study: This study was conducted at the Sahara Medical College, Narowal and Imran Idris Teaching Hospital Sialkot Medical College, Sialkot during Jan 2019 to April 2020.Materials and Methods: Prospective work on successive cases of primary pterygium (Jan 2019 to April 2020) random into two adjuvant groups: (1) During operation zero point zero two percent mitomycin C for five minutes or (2) LCAU. Patients were followed for occurring again (defined as consisting of fibers and conducting cells tissue invading the cornea >one point five mm) and problems for a period of one year. The written informed consent was taken before taking history and examination. Ethical Committee Permission was consider before collecting the findings and get publishing in Medical Journal. The findings were analyzed for results by SPSS version 20.Results: One fifty eyes in one fifty patients who completed the study were random to receive mitomycin C (n = seventy five) and LCAU (n = seventy five). There were twenty again occurring (thirteen point thirty three percent) in the mitomycin C group and only one again occurring (zero point six percent) in the LCAU group. There was a statistically significant difference in the occurring again rate between the two groups (p = zero point zero four). There were a total of three cysts of conjunctiva, three symblepharon, one a mass of granulation tissue, and one dent. No other visually significant issues were seen in either group.Conclusion: This study indicated that LCAU has given good findings in terms of success but it does not give better results in cases of recurrence. Simple excising followed by Mitomycin C or LCAU are both without causing death effects and appreciative for pterygium excision.